Influence of absorption saturation on the shape of CdSe absorption edge - Kulish, M.R.; Malysh, M.I.; Isaienko, G.L.; Litvinova, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Influence of light polarization on absorption saturation for wurtzite modification CdSe has been investigated. It has been ascertained that the size of blurring the fundamental absorption edge for wurtzite modification CdSe is determined by the non-equilibrium electron filling both the conduction band extremum, when the energy of photons h is higher than the bandgap energy Eg, and the density-ofstate tail caused by the presence of static disorder, when the hν < Eg. The density-of-state tail resulting from the presence of dynamic disorder is not filled with electrons because of continuous changes of the dynamic potential relief value in time. In the high-energy spectral region, change in the absorption coefficient is limited by the stimulated emission processes.